Eating disordered behaviours in portuguese athletes: the influence of personal, sport, and psychological variables - Gomes, António Rui (2011)
Objective: This study describes eating disordered behaviours in a sample of Portuguese elite athletes and analyses the impact of personal and sports factors on those eating disordered behaviours. Method: Two hundred and ninety athletes (51.7% males) practicing collective (64.8%) and individual sports have been included. The evaluation protocol included the Eating Disorder Examination Questionnaire; the Sport Condition Questionnaire; the Sport Anxiety Scale; the Task and Ego Orientation in Sport Questionnaire; the Cognitive Evaluation of Sport–Threat Perceptions; and the Self-Presentation Exercise Questionnaire. Results: Females, athletes with a higher body mass index, and those with a desire to weigh less, reported more eating disordered behaviours. No relation with sports variables was found. Finally, a higher prevalence of eating disorders behaviour was predicted by lower satisfaction in terms of body shape and physical appearance, higher anxiety and impression motivation. Conclusion: Personal characteristics of athletes, as well as their body satisfaction, anxiety, impression motivation and threat perception, and coach comments on their weight, represent dimensions that could raise the risk for eating disorders.